INTEGRATED NUTRIENT MANAGEMENT IN CARROT (DAUCUS CARROTA L.) UNDER NORTH EASTERN TRANSITIONAL TRACK OF KARNATAKA - G. PATIL, ANAND; RAJKUMAR, M (The Bioscan, 2015)
A field experiment was conducted at College of Horticulture, Bidar during rabi season consequently for three years (2009-2011) to study the INM in carrot. Among the different treatments, the application of 50% RDF + 25% N through FYM + 25% N through vermicompost recordedsignificantly higher rootyieldof carrot (24.10 t ha-1) compared to rest of the treatments. The highest B: C ratio (7.77) was noticed in 100% RDF alone compared to other treatments. After three years of experiments on same site, combined usage of organic manure with inorganic fertilizers is not only help to improve the yield of carrot but also help in conserving the soil health.